Design and Build Onion Cracker Drying Rack Krajan Hamlet, Randuagung Village, Singosari District - Wahju Wulandari; Shaifany Fatriana Kadir; Sodik; Mochammad Rivan Satriawan (IMPOWERMENT SOCIETY, 2023)
Home business is one of the driving forces of the economy in Indonesia, but its existence is always faced with various problems, including production, equipment, management, and marketing. One of the home businesses in the class of onion crackers owned by Yuyun's mother is located in RT 03 RW 05 Krajan Hamlet, Randuagung Village, Singosari District. This business is an income field for the surrounding community because the production process is simple, so, in the drying process, onion crackers only use a makeshift base with bamboo as a support for cracker bases. This business is an income field for the surrounding community because the production process is simple, so, in the drying process, onion crackers only use a makeshift base with bamboo as a support for cracker bases. The cracker dryer mat is the most crucial means to obtain a completely dry and hygienic cracker result. The purpose of community service is to solve the problem of cracker drying racks. Solutions designing and manufacturing cracker dryers with rack models. The implementation method is by collaborating with partners and students to make a more modern and innovative onion cracker drying rack from elbow iron and Kalimantan wood, making cracker mats from filter nets and hygienic as many as 25 units. The results obtained dry crackers are evenly distributed and cleaner, the shelves are more efficient to accommodate the crackers to be dried in the sun, the production capacity tool increases by 46% of the increased production amount and the revenue rise to 70%.